Maximizing udder health through a selection index: a focus on udder traits in Italian Mediterranean Buffaloes - Johanna Ramírez Díaz; Roberta Cimmino; Rossi Dario; Zullo Gianluigi; Neglia Gianluca; Altieri Damiano; Mayra Gómez; Stefano Biffani; Giuseppe Campanile (Revista Científica)
The Italian Mediterranean Buffalo is the most important buffalo’s breeds for milk production and its derivatives, which has a selection program implemented more than 20 years ago. The selection is based on an aggregate index that includes dairy, mozzarella yield, and functional traits. The improvement of udder conformation (UC) traits is an aspect that plays an essential role in udder health and longevity; it is of great interest due to its direct relationship with economic losses caused by mastitis or poor milkability. The aim of this study was the development of an aggregate selection index (ASI) considering MP (milk production), MSCS150 (geometric mean of somatic cell score at 150 days in milk), and UC traits (fore udder attachment– FUA; rear udder width– RUW; rear legs height– RLH; teat direction – TD; teat length – TL and teat position – TP). The first step was to estimate the genetic (co)variances between the UC, MP, and MSCS150 traits and to estimate the relative weight for each UC trait. The phenotypic records of 15,275 females and a pedigree with 43,395 animals were used. A multitrait animal model that included CG (herd-year-calving season), calving month, and parity as fixed effects, and the animal as a random effect was used. The estimated heritability for MP and MSCS150 were 0.391 and 0.134, respectively, and varied between 0.11 and 0.23 for UC traits. Low negative genetic correlations were observed between MP and RLH (−0.119), the same pattern between MSCS150 and RLH (−0.350) and MSCS150 and FUA (−0.220). A positive correlation was found between FUA and MP (0.4272) and MP and RUW (0.645). Using ASI as selection criteria, an annual reduction of −0.03 is expected for MSCS150 and an increase of 0.26 kg for MP. During a selection period of ten years, the expected cumulative genetic gains would be -0.32 for MSCS150 and an increase of MP in 2.57 kg. Selective breeding programs aim to improve specific traits over time by selecting individuals with desirable genetic characteristics as parents of the next generation. According to the results, by focusing on RUW, RLH, and TD traits, genetic improvements are expected to lead to reduced severity of MSCS150 while maintaining or increasing milk production.